Інформаційна система забезпечення оптимального аероіонного режиму у приміщенні - Строкань, Оксана Вікторівна; Строкань, Оксана Викторовна; Strokan, Oksana; Мірошниченко, Микола Юрійович; Мирошниченко, Николай Юрьевич; Miroshnychenko, Mykola (My University, 2018)
UK: У статті виконано обгрунтування необхідності створення оптимального режиму аероіонізації у приміщені. Запропоновано вирішити проблему створення оптимального режиму аероіонізації в приміщені шляхом розробки відповідної інформаційної системи, яка забезпечить можливість автоматичного визначення концентрації аероіонів в робочій зоні від джерел аероіонів. EN: In the article the necessity of creation of optimal mode of aeroionization in the working area. Describes the effect of the concentration of negative aeroions on the human organism. It is proposed to solve the problem of creating optimal mode of aeroionization in the working area through the development of a corresponding software module, which would provide the possibility to automatically determine distribution of concentration of ion in the working area from single and multiple airionizator and determine where to install airionizator in this area depending on input parameters.
Keywords: аероіонізація; мікроклімат; робоче середовище